Factors affecting supplier selection in the Malaysian fresh produce industry - Mohd Nawi, Nolila; Mohamed, Zainal Abidin (American-Eurasian Network for Scientific Information, 2013)
The selection of trading partners is one of the most important decisions to make in business-to-business marketing. Previous studies indicated that quality; price and the ability to deliver are generally regarded as the most important criteria by which organisational buyers evaluate their potential suppliers. Thus, the aim of this study is to determine the factors affecting supplier selection from the buyer's perspective within the Malaysian fresh produce industry. A survey was conducted in two major wholesale markets in Malaysia using a simple random sampling technique. A total of 53 wholesalers represented the buyers were selected and interviewed via structured questionnaire. Data was analysed using descriptive and factor analysis. The results from the survey indicated that the ability of the supplier to offer a fair price is the most important criteria used by the wholesalers when selecting their potential supplier while, sharing marketing information are the least. Factor analysis using principal component method revealed four factors that collectively described wholesaler's perspective on their supplier selection namely quality of produce, ability to supply, appearance of produce and competitiveness. Suppliers must be able to fulfil these important attributes as indicated by the buyers to remain competitive and a long-term relationship in the market.